Restoring nature in engineering structure : a modelling of Kuching bypass floodway - Mah, Yau Seng (Springer Science, 2011)
Engineering infrastructure development usually causes disturbances to environment. Rarely, the natural processes are restored in these physical structures. This paper highlights examples of coexistence of nature and engineering structure in flood control systems in US and Hong Kong, and treats the idea on a new project, a bypass flooding system in Kuching, Malaysia by computer simulation. When the Kuching floodway idles during normal days, it is modelled as a pond to match the surrounding peat swamp. The in-channel pond requires lower flow, allowing the downstream river its natural flows. The modelling simulation shows plausible results to put back nature in man-made system to restrain saline intrusion and problem of low flushing due to flow diversion. With that, it is time to call for the society, particularly the engineering communities to adopt a more nature-sensitive approach in engineering designs.